5
$\begingroup$

I calculated the number of labeled Abelian groups of order $N$ (i.e., the number of distinct, abelian group laws on a set of $N$ elements). This sequence is given by OEIS A034382, but my solution differs at $N=16$.

Please point out mistakes or confirm my solution?


Let $C_n$ be a cyclic group of order $n$, $Aut(G)$ be an automorphism set of $G$.

Tthe number of labeled Abelian groups of order $N$ is $\displaystyle{\sum \frac{N!}{\# Aut(G)}}$ where G runs representative of isomorphic equivalence.

I got

$\displaystyle{ \# Aut(C_{p^n}^k)=p^{(n-1)k^2}\prod_{j=0}^{k-1} (p^{k}-p^{j}) }$

and

$\displaystyle{ \# Aut(\prod_i C_{p^{n_i}}^{k_i}) =\prod_i \left( (p^{(n_i-1)k_i^2}\prod_{j=0}^{k_i-1} (p^{k_i}-p^{j})) ( \prod_{j\neq i} p^{\min(n_i,n_j)k_j} )^{k_i} \right) }$.

From the fundamental theorem of finite abelian groups, There are 5 groups for $N=16$: $C_{16}, C_2 \times C_8, C_4^2, C_2^2\times C_4, C_2^4$.

Therefore, the number of groups that are isomorphic to each group is:

  • $C_{16}$ ... $\displaystyle{\frac{16!}{8}}$
  • $C_2 \times C_8$ ... $\displaystyle{\frac{16!}{(1\times 2)\times (2\times 4)}}$
  • $C_4^2$ ... $\displaystyle{\frac{16!}{16\times 3\times 2}}$
  • $C_2^2\times C_4$ ... $\displaystyle{\frac{16!}{((3\times 2)\times 2^2)\times (2^2\times 2)}}$
  • $C_2^4$ ... $\displaystyle{\frac{16!}{15\times 14\times 12\times 8}}$

Sum of them is $4250979532800$. OEIS says $4248755596800$.

$\endgroup$

migrated from mathoverflow.net Sep 13 at 12:07

This question came from our site for professional mathematicians.

  • 1
    $\begingroup$ It's only off by one-twentieth of one percent – what's the big deal? $\endgroup$ – Gerry Myerson Sep 12 at 6:16
  • $\begingroup$ I'm sorry that this should post to Mathematics stack exchange. I'll delete this question soon. $\endgroup$ – sugarknri Sep 12 at 10:59
  • 3
    $\begingroup$ It may be an error in OEIS. In either case it's a good question, and I don't support the close votes. $\endgroup$ – Max Alekseyev Sep 12 at 12:38
  • 1
    $\begingroup$ In case it's a good question, it would benefit from being better introduced... it starts with 3 sentences which look unrelated. The notion in the title is not defined. Also the title should not be considered as the 1st line of the post: the post should be meaningful without reading the title. $\endgroup$ – YCor Sep 12 at 23:17
  • $\begingroup$ @YCor Thank you for the advice about the format. I change text. If the text is still not clear, It may be because of my English ability. $\endgroup$ – sugarknri Sep 13 at 3:35
8
$\begingroup$

There is a different formula for $\#\mathrm{Aut}(\prod_i C_{p^{n_i}}^{k_i})$ given in the paper Automorphisms of Finite Abelian Groups by Hillar and Rhea: $$\#\mathrm{Aut}(\prod_{t=1}^m C_{p^{e_t}}) = \prod_{t=1}^m (p^{d_t} - p^{t-1}) p^{e_t(m-d_t) + (e_t-1)(m-c_t+1)},$$ where $1\leq e_1\leq e_2\leq \cdots\leq e_m$, and $c_t$ and $d_t$ are the minimum and maximum of the set $S_t := \{\ell\ :\ e_\ell=e_t\}$, respectively.

Below I will show that OP's formula is equivalent to the Hillar-Rhea formula.


Let $d_0:=0$. It can be seen that the $k_i$'s are the nonzero elements of the multiset $\{ d_1-d_0, d_2-d_1, \dots, d_m-d_{m-1}\}$ and the $n_i$'s are the corresponding elements of $\{e_1,e_2,\dots,e_m\}$. Define $s_0=0, s_1, \dots, s_q$ be the indices such that $k_i = d_{s_i} - d_{s_{i-1}}$ and $n_i = e_{s_i}$. Vice versa, $d_{s_i} = k_1+\dots+k_i$ and $c_{s_i} = d_{s_{i-1}}+1$.

First consider these parts of the two formulas: $$\prod_{i=1}^q \prod_{j=0}^{k_i-1} (p^{k_i} - p^j) = \prod_{i=1}^q p^{k_i(k_i-1)/2} \prod_{j=0}^{k_i-1} (p^{k_i-j} - 1)$$ and $$\prod_{t=1}^m (p^{d_t} - p^{t-1}) = p^{m(m-1)/2}\prod_{t=1}^m (p^{d_t-t+1} - 1).$$ It is easy to see that the multisets $\{ k_i - j : 0\leq j \leq k_i-1, 1\leq i\leq q \}$ and $\{ d_t - t +1\ :\ 1\leq t\leq m \}$ are the same, since the $t$-th element in the sequence $$k_1 - 0, k_1 - 1, \dots, 1, k_2 - 0, k_2 - 1, \dots, 1, \dots$$ equals $d_t-t+1$.

Now it remains to prove the equality for the powers of $p$ in the two formulas, i.e. $$\sum_{i=1}^q \bigg(k_i(k_i-1)/2 + (n_i-1)k_i^2 + \sum_{j\ne i} \min(n_i,n_j)k_ik_j\bigg) = m(m-1)/2 + \sum_{t=1}^m \big(e_t(m-d_t) + (e_t-1)(m-c_t+1)\big).$$ In the l.h.s. we have $$\sum_{i=1}^q \sum_{j\ne i} \min(n_i,n_j)k_ik_j = 2\sum_{i=1}^q n_i k_i \sum_{j>i} k_j=2\sum_{i=1}^q n_i k_i (m-d_{s_i}).$$ In the r.h.s. we have \begin{split} \sum_{t=1}^m \big(e_t(m-d_t) + (e_t-1)(m-c_t+1)\big) &= \sum_{i=1}^q k_i\big(e_{s_i}(m-d_{s_i}) + (e_{s_i}-1)(m-d_{s_{i-1}})\big) \\ &= \sum_{i=1}^q k_i\big(n_i(m-d_{s_i}) + (n_i-1)(m-d_{s_{i-1}})\big)\\ &=\sum_{i=1}^q k_i\big(n_i(m-d_{s_i}) + (n_i-1)(m+k_i-d_{s_i})\big)\\ &=2\sum_{i=1}^q k_i n_i(m-d_{s_i}) + \sum_{i=1}^q \big( (n_i-1)k_i^2 - (m-d_{s_i})k_i\big). \end{split} Finally, we notice that $$\sum_{i=1}^q k_i(k_i-1)/2 = m(m-1)/2 - \sum_{i=1}^q (m-d_{s_i})k_i$$ since $m=k_1+k_2+\dots+k_q$ and $m-d_{s_i} = k_{i+1}+k_{i+1}+\dots+k_q$. QED


So, we can conclude that OEIS A034382 did indeed contain an error in its 16-th term. Now it's corrected.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.